Dialektika Manajemen Diri dan Komunikasi dalam Konstruksi Employability Skills Warga Belajar di SKB Kota Malang: The Dialectic of Self-Management and Communication in the Construction of Employability Skills of Students at SKB Malang City - Dwi Hera Prasetya Ningsih; Hardika Hardika; Ahmad Ahmad (ITScience (Information Technology and Science), 2026)
Employability skills are crucial for improving the work readiness of graduates of non-formal education. However, the development of these skills in Package C learners is often understood in a linear, quantitative manner, thereby failing to explain the underlying social processes. This study aims to understand the dialectic between self-management and communication in shaping the employability skills of Package C learners at the SKB Malang City. The study used a qualitative, interpretive case study design. Data were obtained through semi-structured interviews with 10 learners, observations of learning, and reflective documentation. Analysis was conducted using thematic analysis through an iterative process of coding, categorisation, and theme extraction. Data credibility was maintained through triangulation and member checking. The study found that self-management functions as an internal regulation that fosters consistency, perseverance, and responsibility in learning. At the same time, communication serves as a social space that strengthens learners’ self-confidence, collaborative abilities, and professional identity. The integration of these two dimensions yields adaptive, context-specific employability skills. Employability skills are not formed in isolation, but through the repeated interaction of self-regulation and communication practices within the dynamics of non-formal learning. The employability skills of Package C students are a social-reflective construct that develops through a dialectical process between self-management and communication skills. These findings broaden the perspective on developing employability skills in equivalency education, moving from a linear to a constructive, contextual approach that better reflects students’ learning experiences.